Innovating Journalism Education with Podcasts: A Revolutionary Teaching Tool - Palomino-Flores, Paola (2023)
As digital platforms continue to rapidly replace traditional forms of media; journalism students require new skills to succeed in their future careers. This article examines the innovative use of podcasts as a teaching tool in journalism education, offering students the opportunity to develop storytelling and digital communication skills. The benefits and challenges of integrating podcasts into the curriculum are discussed, along with examples of successful podcasting projects. The importance of innovation in journalism education is emphasized to keep up with the changing media landscape. The potential of podcasts to transform journalism education and prepare students for a career in the digital age is underscored. By exploring the use of podcasts as a revolutionary teaching tool in journalism education, this paper reveals a new frontier in the field.